Medios comunitarios informativos en los procesos sociales cantonales - Candelario Vera, Andreina Maribel (2020)
The main objective of the present research work is to analyze the importance of the creation of a community radio to address the communicational needs of the farmers of the San Juan parish, Puebloviejo canton, Los Ríos province. Therefore, a mixed approach was applied, using an explanatory, descriptive and field research study, in order to listen and solve the problems faced by the inhabitants of that sector through this establishment. Surveys were conducted on a sample of 98 farmers, from the Quinta Dianita farm, located in the province of Los Ríos, San Juan, canton Puebloviejo parish. In addition to 2 interviews with communication professionals…….